The evaluation of toxic effect (LC 50) of endosulfan on female crab Brytelphusa guerini. - B, Deshai R; P, Katore B; D, Shinde V; E, Ambore N (Journal of Experimental Sciences, 2013)
Man with extraordinary intellectual capability conquered the age; old traditional world by establishing modern technological world to cater the needs of all the human beings. As the most intelligent man acquired supremacy and mastery over each and every object on the earth and mode them to keep under his control. The paper deals with the organochlorine pesticide which is regularly used in agricultural purpose interact directly or indirectly with the biosphere spoils the biota flora and the fauna. The endosulfan toxicity calculated by LC 50 and effect of death rate found on the fresh water crab species Barytelphusa guerini. The paper details with mortality rate of experimental animals 50% at each 24 hours. It is calculated by statically and presented by graphically and tabulated by tables.